Finance and Development, June 1968. (Finance and Development; Finance and Development ;, 1968)
This paper discusses origins of recent estimates of capital requirements for development and highlights some of the issues involved. The paper highlights that there are two possible approaches to making estimates of capital requirements for development. Both approaches are based on the idea that increased income and wealth depend fundamentally upon the application of more capital, either to increase output directly when used in combination with local resources, or indirectly when the use of such capital will lead to a more effective use of other resources.